Manajemen stres dalam meningkatkan kesehatan mental mahasiswa - Nabila, Az Zahra (Maliki Interdisciplinary Journal, 2024)
Stress is a significant challenge for university students that can impact their mental health. This article discusses the importance of stress management to improve students' mental health, identifying stressors such as academic pressure, financial problems, social pressure, and lifestyle changes. The effects of poorly managed stress include anxiety disorders, depression, sleep problems, and substance abuse. The article also outlines various effective strategies for managing stress, including relaxation techniques, regular exercise, time management, social support, healthy diet, adequate rest, cognitive-behavioral techniques, emotional management, hobbies and creative activities, problem-solving skills, and professional counseling and assistance. The implementation of stress management programs on campus, such as orientation programs, training and workshops, counseling services, support groups, and extracurricular activities are also discussed. Through effective stress management, students can improve their mental health, reach their full potential, and enjoy a positive and fulfilling educational experience.